Fully Controlled 6 Meters per Pixel Mosaic of Mars's South Polar Region. Issue 10 (23rd October 2020) - Robbins, Stuart J.; Kirchoff, Michelle R.; Hoover, Rachael H.
Abstract: The Mars Reconnaissance Orbiter ( MRO ) spacecraft has been in operation around Mars since March 2006. The Context Camera (CTX), aboard MRO, has returned over 110, 000 images of Mars at ≈5–6 m/px, providing nearly global coverage. Based on our work, reconstruction of MRO 's orbit and camera pointing from ground tracking are offset from the Mars global coordinate system, with the 95th percentile of test points offset by ≈850 m, corresponding to ≈150 CTX pixels. While the original level of accuracy is potentially useful for some applications, providing relative control (image‐to‐image) and absolute or full control (image‐to‐ground reference) greatly improves the utility of the data. As a proof‐of‐concept, we have fully controlled all usable images of Mars Chart 30, Mare Australe, which is poleward of 65°S. This represents 4.7% of Mars's surface area and comprises 9, 652 images (≈8% of the CTX catalog as of PDS release #48). The control was produced through a mixture of automated code and manual adjustment and validation, and mosaics were produced with manual input to provide a useful product with the best, most consistent images on top. The data—mosaics and updated SPICE kernels—are available to the community through NASA's Planetary Data System (PDS) Imaging and Cartography Annex. The workflow developed for this product is applicable to the remainder of Mars and other planetary bodies. Plain Language Summary: Creating a mosaic from spacecraft images of a planetary surface requires knowing a lot of geometry: Where the spacecraft was, how it was pointed, and how it was moving; and that same information is needed for the camera that took the images. This information is needed to properly place each pixel at the correct location on a planet's surface. These geometry data can be coarsely estimated based on tracking the spacecraft from Earth and knowing how it and its camera system were commanded. However, images projected from them can have significant offsets relative to each other and relative to other data sets, limiting their usefulness. Software exists to match the same planetary feature on multiple images, and then determine a better solution for the spacecraft and camera geometry. We developed a workflow that automates running much of that software, and we applied it to the south polar region of Mars, about 5% of the planet. There are nearly 10, 000 images in the mosaic, and the mosaic itself is 255 billion pixels, rendered at a ground scale of 6 m/px. Each pixel has an average uncertainty in its location of ≈10 m, significantly better than ≈500 m uncertainty based on Earth tracking. Key Points: We created a fully controlled CTX mosaic of Mars's south pole, Mare Australe (south of 65°S), tied to MOLA 9, 652 usable images were controlled via 3, 165, 965 tie points with 12, 224, 255 measures (233 points, or 1, 654 measures constrained to MOLA) We provide updated SPICE data for all images in the control network